Heat exchanger network synthesis with process safety compliance under tube rupture scenarios. (June 2022) - Harhara, Ahmed; Faruque Hasan, M.M.
Highlights: A new Safety Rating to quantify the overpressure risk of heat exchangers. MINLP model for mitigating overpressure risk in heat exchanger network synthesis. Dynamic shell pressurization model handles complex exchanger configurations. Conservative Safety Rating achieved via tight piecewise linear underestimator. Case studies reveal overpressure safety achievable without sacrificing economics. Graphical abstract: Abstract: While there exists considerable research on HEN Synthesis (HENS), little attention has been paid to incorporating process safety of HENS at the conceptual design stage. In this work, we extend the optimization-based HENS to incorporate safety using a Safety Rating (SR) to safely navigate dynamic tube rupture scenarios for all plausible heat exchanger matches. This metric allows one to assess the risk of overpressure resulting in failure of the equipment. To avoid such complexity, we develop a piecewise linear approximation of SR using data obtained from a dynamic tube rupture model. Our approximation is such that it always provides guaranteed and tight underestimation of the SR values, thereby ensuring process safety. Applying the methodology, we obtain HEN configurations with lowest costs that can safely handle overpressure events for the entire network. By rethinking how to mitigate process safety challenges using systems approaches, plants can incorporate safer designs for minimal cost.